Characteristics of migraine patients with Migraine Disability Assessment (MIDAS) scores in real-world clinical practice - Victoria Chia; Alina Bogdanov; Akeem Yusuf; Lee Kallenbach (SAGE Publishing, 2020)
Background: Better understanding of migraine treatment in US clinical practice could be facilitated by availability of Migraine Disability Assessment (MIDAS) questionnaire results collected in routine care. We present results for migraine patients with MIDAS collected in routine clinical practice through an electronic medical record (EMR) system that presented the MIDAS questionnaire as an electronic form during the patient office encounter. The purpose of this retrospective observational study was to gain better understanding of migraine disability and migraine treatment patterns in US real-world clinical practice. Methods: In this EMR database study, patients were required to have 12 months baseline time for review of patient and clinical characteristics. Adult patients with documentation of migraine with subsequent MIDAS questionnaire data collected between March 2017 and September 2018 were included. Based on MIDAS responses patients were categorized into grade I-little or no disability, grade II-mild disability, grade III-moderate disability, and grade IV-severe disability. Results: This study included 2731 migraine patients with MIDAS results. Overall, 2309 (84.5%) were female with an average age of 46.7 years. Distribution by disability grade was 1161 (42.5%) little or no disability, 424 (15.5%) mild disability, 477 (17.5%) moderate disability, and 669 (24.5%) severe disability. Compared to overall, a larger proportion of patients with severe disability had baseline treatment with acute (71.3% vs. 67.6%) or preventive medications (70.4% vs. 62.0%) and to be on 3+ acute (9.4% vs. 7.0%) or 3+ preventive therapies (17.0% vs. 14.5%). Conclusion: Availability of MIDAS results in usual care provides additional insight into migraine care.